How the spirit became God the mosaic of early Christian pneumatology - Hughes, Kyle R.; Bates, Matthew W. 1977- (Eugene, Oregon Cascade Books, 2020)
The problem of the Holy Spirit -- The Spirit and divine testimony -- The Spirit and Christian identity -- The Spirit and person language -- The Spirit and the divine economy -- The Spirit and full divinity -- The invitation of the Holy Spirit.
"In How the Spirit Became God, Kyle Hughes tells the often-neglected story of how and why the early church came to recognize that the Holy Spirit was a distinct divine person. While the subject of Christ's divinity is a popular topic in church and academy alike, the notion of the Spirit's divinity remains a mysterious yet intriguing question for many Christians today. Focusing on major pneumatological innovations from Pentecost through the Council of Constantinople in 381, Hughes examines how biblical interpretation and the lived experience of the Spirit contributed to the development of this important, and yet often overlooked, aspect of trinitarian theology. This important contribution not only explains, from a historical yet accessible perspective, the development of early Christian pneumatology but also challenges readers to apply these insights from the church fathers to engaging with the person of the Holy Spirit today."--Back cover
Includes bibliographical references (pages 141-149) and indexes
Keywords: Holy Spirit; Trinity; God (Christianity); Theology, Doctrinal; Holy Spirit -- History of doctrines -- Early church, ca. 30-600